Produto audiovisual de extensão: Arquivo Público do Estado do Pará - MARTINS, Átila Clivea da Silva (2023)
Diffusion is an archival function that provides access to archival documents where information is recorded that are part of the construction of the stories and memories of a society. Although it is relevant to history and memory, the archives and their collections are little known by society. Therefore, the objective is to carry out the dissemination of the documentary collection of the Public Archive of the State of Pará, due to its importance to the social memory of the Amazon region, more specifically to the State of Pará. Thus, through a technical visit to collect audios, videos and photographs, the result was an audiovisual product that tells the memories and narrates the stories of the Public Archive of the State of Pará.